An evaluation of International Reference Ionosphere electron density in the polar cap and cusp using EISCAT Svalbard radar measurements - Bjoland, Lindis Merete; Belyey, Vasyl; Løvhaug, Unni Pia; La Hoz, Cesar (Annales Geophysicae, 2016)
Incoherent scatter radar measurements are an important source for studies of ionospheric plasma parameters. In this paper the EISCAT Svalbard radar (ESR) long-term database is used to evaluate the International Reference Ionosphere (IRI) model. The ESR started operations in 1996, and the accumulated database up to 2012 thus covers 16 years, giving an overview of the ionosphere in the polar cap and cusp during more than one solar cycle. Data from ESR can be used to obtain information about primary plasma parameters: electron density, electron and ion temperature, and line-of-sight plasma velocity from an altitude of about 50 and up to 1600 km. Monthly averages of electron density and temperature and ion temperature and composition are also provided by the IRI model from an altitude of 50 to 2000 km. We have compared electron density data obtained from the ESR with the predicted electron density from the IRI-2016 model. Our results show that the IRI model in general fits the ESR data well around the F2 peak height. However, the model seems to underestimate the electron density at lower altitudes, particularly during winter months. During solar minimum the model is also less accurate at higher altitudes. The purpose of this study is to validate the IRI model at polar latitudes.